2016
DOI: 10.3171/2015.8.spine15129
|View full text |Cite
|
Sign up to set email alerts
|

Successful management of a giant anterior sacral meningocele with an endoscopic cutting stapler: case report

Abstract: Anterior sacral meningoceles (ASMs) are rare defects in the sacrum with thecal sac herniations and symptoms that commonly include constipation, dysmenorrhea, and urinary disturbances. An ASM causing hydronephrosis and acute renal failure from compression of the lower portion of the urinary tract is a rare clinical entity. Only one other case has been reported. The authors present the case of a 37-year-old man admitted for obstructive renal failure and hydronephrosis due to a giant ASM that measured 25 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
23
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 25 publications
(27 reference statements)
0
23
0
Order By: Relevance
“…Considering the complexity of surgery to correct an ASM, its management should be based on the severity of patient's symptoms (Hanna and Morandi, ; Ashley and Wright, ; Sunna et al, ). Asymptomatic or mildly symptomatic patients may do better with a conservative approach and follow‐up as needed.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the complexity of surgery to correct an ASM, its management should be based on the severity of patient's symptoms (Hanna and Morandi, ; Ashley and Wright, ; Sunna et al, ). Asymptomatic or mildly symptomatic patients may do better with a conservative approach and follow‐up as needed.…”
Section: Discussionmentioning
confidence: 99%
“…This lesion is seen with equal signal intensities of cerebrospinal fluid on all MR sequences and is usually unilocular. [28] Song et al mistook a SHC with a GCT on MR. [15] The most common GCTs site is distal femur and proximal tibia in 50%-65%, but can affect sacrum in 4%-9% of cases. [29] The MR T2-weighted images show a heterogeneous high signal with areas of low-signal intensity (variable) due to hemosiderin or fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…We reviewed all six reported cases of ASM with TSC, all of whom underwent untethering surgery (Table ). In those cases, urinary symptoms were resolved in three patients after TSC release, whereas the other three cases remained symptomatic despite improved neurological function in the extremities . We investigated the MRI features that are associated with prognosis for LUT function and found that in all patients who remained symptomatic, MRI showed syringomyelia, which was not found in cases with symptom alleviation.…”
Section: Summary Of the Present Case And Five Previous Cases Of Asm Wmentioning
confidence: 97%
“…ASM is divided into two groups based on the presence or absence of TSC. Cases of ASM presenting with TSC are much rarer, and are typically identified by neurological symptoms and/or dysuria in patients with a wide age range . In such cases, untethering surgery is carried out in patients with neurological symptoms in the extremities.…”
Section: Summary Of the Present Case And Five Previous Cases Of Asm Wmentioning
confidence: 99%